Simulation of Electron Energy Spectra of a Biased Paracentric Hemispherical Deflection Analyzer as a Function of Entry Bias: Effects of Misalignments - O. Sise (Journal of Spectroscopy)
The performance of a biased paracentric hemispherical deflection analyzer (HDA), including fringing fields and their effect on focusing and energy resolution, is investigated using numerical methods. Electron energy spectra are calculated for three entry positions R0=84 mm, 100 mm, and 112 mm and compared with the recent experimental measurements. In both experiment and calculation, the two different paracentric entry positions R0=84 mm and R0=112 mm, on either side of the mean radius of 100 mm, are found to have a base energy resolution of about two times better than the conventional centric entry position R0=100 mm. In order to explain the discrepancies (6–30%) between the simulated and the experimental resolutions the focusing characteristics are further investigated for different displacements of the input lens (ΔR0) with respect to the entry position R0 and the tilted input beam axis by αshift in the dispersive direction. We have found that the blame does not in fact lie with the theory and we have shown that the input lens may have been misaligned in the experiment. Slight misalignments affect both the true energy resolution measurement and the transmission of the beam.